Induced Seismicity by Groundwater Extraction at the Dead Sea Fault, Jordan. Issue 1 (25th January 2023) - Shalev, E.; Wetzler, N.; Shatanawi, A.; Rödiger, T.; Kurzon, I.; Lyakhovsky, V.; Salameh, E.; Siebert, C.
Abstract: The earthquake sequence, with a maximum earthquake magnitude of M W 3.8, that occurred during January–February 2022 at the northern Dead Sea fault, is shown to be induced by extensive groundwater abstraction in Wadi Al‐Arab basin. Wadi Al‐Arab basin, which is bordered in the west by the Dead Sea fault, has been overexploited by extensive groundwater abstraction causing significant drawdowns. Relative earthquake relocation indicates an elongated S‐N sequence subparallel to the Dead Sea fault. We simulate the three‐dimensional hydraulic head changes in the past 40 years at Wadi al Arab basin. Results show that the drawdowns at the Dead Sea fault wells reached a value greater than 180 m. We use these results to further model the poroelastic effects of the drawdown on the stability of the Dead Sea fault using a typical fault architecture including fault core surrounded by damage zone. Upward groundwater drainage through the permeable damage zone leads to compaction and strengthening. Failure on the Dead Sea fault is expected to occur on the impermeable fault core or at the protholith where weakening is expected. Groundwater abstraction in Wadi Al‐Arab basin cause changes of a few MPa in the Coulmb Failure Stress (ΔCFS) and trigger seismicity in these sections. This is the second location along the Dead Sea fault where groundwater abstraction was shown to recently induce earthquakes. With growing demand for water and long lasting droughts in the Middle East, seismicity induced by groundwater abstraction might reoccur in the near future. Plain Language Summary: Earthquakes are shown in many cases to be induced by water injection but they can also be induced by groundwater pumping. We analyze an earthquake sequence that occurred along the Dead Sea fault during January–February 2022 and show that it was induced by groundwater pumping. The location of the earthquakes form an elongated cluster subparallel to the trace of the main plate boundary. Groundwater levels in the area have dropped by more than 100 m in the last 40 years due to extensive pumping. We model the effects of pumping on groundwater levels in the basin and use these results to simulate the triggered seismicity on the active Dead Sea fault. This is the second place along the Dead Sea fault where groundwater overexploitation has triggered seismicity. With growing demand for water and long lasting droughts in the Middle East, seismicity induced by groundwater abstraction might reoccur in the near future. Key Points: Earthquake sequence that occurred at the northern Dead Sea fault is shown to be induced by extensive groundwater abstraction An elongated earthquake sequence, subparallel to the Dead Sea fault occurred in two main clusters separated by 1 km and 18 days apart Failure on the Dead Sea fault is predicted to occur on the impermeable fault core or at the protholith but not in the damage zone